Media Sosial yang Dibenci yang Ditakuti - Watie, Errika Dwi Setya (Jurnal The Messenger, 2012)
Social media users came from every part of society. The presence and acceptance of social media, of course, not only have an impact on the lives of individual users directly, but it is also have an impact on the lives of the state concerned. It should be understood, that the mass media has the ability to build the image and opinions in the minds of users. Currently there are 6 types of social media are present in the community. the negative impact of social media in fact also present along with the increasing positive impact. The number of negative cases that accompany the presence of social media, making social media seems to be something scary. Therefore, should be wise in using social media.